Romantic Science and the Experience of Self: Transatlantic Crosscurrents from William James to Oliver Sacks - Martin Halliwell (New York : Routledge, 2016)
Annotation
Keywords: Psychology History 20th Centuary; Romanticism Influence; Psychology